AIS’s Alignment amd Businsess Performance of Firms A Multigroup Analysis with SEM model - Thu Ba, Tran (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
The paper studies the model that assesses impacts and contributions of the factors of information request (IR) and information capacity (IC) in the Accounting Information System’s alignment (AIS).  The empirical research carried out in 398 enterprises which are divided into a group of small sized enterprises and a group of medium and large sized enterprises in the Southern key economic areas of Vietnam indicates that IR and IC make positive contributions to AIS’s alignment. AIS’s alignment also has a strong impact on firms’ business performance (P). In addition, a large difference between the two groups of enterprises regards AIS’s alignment and influence on firms’s business performance is also detected. The paper concludes with a number of orientations suggested by the author in developing AISs that are capable of processing and meeting demands for information of administrators helping improve Vietnamese enterprises’ business performance in the international integration. Keywords Business performance, accounting information system, assessment model, impact factors, SEM. References [1] Noor Azizi Ismail, Malcolm King, “Firm performance and AIS alignment in Malaysian SMEs”, International Journal of Accounting Information Systems, 6 (2005), 241-259. [2] Louadi, Mohamed El, “The Relationship Among Organization Structure, Information Technology and Information Processing in Small Canadian Firms”, Canadian Journal of Administrative Sciences, 15 (1998) 2, 180-199. [3] Deepak Khazanchi, “Information technology (IT) appropriateness: The contingency theory of “FIT” and IT Implementation in small and medium enterprises”, Journal of Computer Information Systems, 45 (2005) 3, 88-95. [4] Abernethy, M. A., Guthrie, C. H., “An empirical assessment of the “fit” between strategy and management information system design”, Journal Accounting & Finance, 34 (1994) 2, 49-66. [5] Amidu, M., Abor, J., “Accounting Information and Management of SMEs in Ghana”, African Journal of Finance and Management, 14 (2005) 1, 15-24. [6] Bollen, K. A., Structural equations with latent variables, John Wiley & Sons, 2004. [7] Bolon, D. S., “Information processing theory: Implications for health care organisations”, International Journal of Technology Management, 15 (1998) 3, 211-221. [8] Cragg, P., King, M., & Hussin, H., “IT alignment and firm performance in small manufacturing firms”, The Journal of Strategic Information Systems, 11 (2002) 2, 109-132. [9] Gul F.A., “The effects of management accounting systems and environmental uncertainty on small business managers’ performance”, Accounting and Business Research Journal, 22 (1991) 85, 57-61. [10] Gul F.A., Chia Y.M., “The effects of management accounting systems, perceived environmental uncertainty and decentralisation on managerial performance: A test of three-way interaction”, Accounting, Organizations and Society,19 (1994) 4/5, 413-26. [11] Raymond L., Pare G., Bergeron F., “Matching information technology and organisational structure: An empirical study with implications for performance”, European Journal of Information Systems, 4 (1995), 3-16. [12] Fuller T., “Fulfilling IT needs in small businesses: A recursive learning model”, International Small Business Journal, 14 (1996) 4, 25-44. [13] Chan Y.E., Huff S.L., Barclay D.W., Copeland D.G., “Business strategic orientation, information systems strategic orientation and strategic alignment”, Information Systems Research, 8 (1997) 2, 125-50. [14] Nguyễn Thị Tố Quyên, “Đo lường mức độ phù hợp của hệ thống thông tin kế toán trong mối quan hệ với hiệu quả hoạt động kinh doanh của các doanh nghiệp tại Thành phố Hồ Chí Minh”, Luận văn Thạc sĩ, Trường Đại học Kinh tế Thành phố Hồ Chí Minh, 2015. [15] Nguyễn Đình Thọ, Nguyễn Thị Mai Trang, Nghiên cứu khoa học trong quản trị kinh doanh, NXB. Thống kê, Hà Nội, 2008, tr. 208. [16] Huỳnh Thị Hồng Hạnh, Nguyễn Mạnh Toàn, “Đánh giá hiệu quả của hệ thống thông tin kế toán”, Tạp chí Kế toán & Kiểm toán, 6 (2013), 11-15. [17] Nguyễn Bích Liên, “Xác định và kiểm soát các nhân tố ảnh hưởng chất lượng thông tin kế toán trong môi trường ứng dụng hệ thống hoạch định nguồn lực doanh nghiệp (ERP) tại các doanh nghiệp Việt Nam”, Luận án Tiến sĩ Kinh tế, Trường Đại học Kinh tế Thành phố Hồ Chí Minh, 2012.